Implementasi Asesmen Nasional Berbasis Komputer (ANBK) pada Siswa Kelas 5 MI Ma’arif 04 Gentasari Kecamatan Kroya Kabupaten Cilacap - Siti Sihatussalamah; Hendri Purbo Waseso (JOIN: Journal of Indonesian Education and Learning, 2025)
The National Assessment is an effort to comprehensively map and assess the quality of learning processes and outcomes in primary and secondary schools throughout Indonesia. The aim of this research is to analyze the implementation of the Computer-Based National Assessment (ANBK) for grade 5 students at MI Ma'arif 04 Gentasari, Kroya District, Cilacap Regency, starting from the planning to evaluation stages. This research uses a qualitative descriptive method. The subjects of this research were madrasa heads, teachers, proctors and students. Data collection techniques were carried out using interviews, observation and documentation. The data analysis technique is carried out by data reduction, data presentation, and drawing conclusions. Meanwhile, data validity testing techniques are carried out using technical triangulation. The research results show that: ANBK preparations in madrasas have been carried out thoroughly, involving various parties and covering various aspects such as personnel management, socialization, simulations and clean rehearsals. In general, the implementation of ANBK runs according to procedures. However, there are several technical obstacles, students' cognitive and psychological abilities that need to be considered. The ANBK results show that the majority of students have reached the minimum competency limits for reading literacy (good), numeracy (medium), character (good), and learning quality (medium). Overall, ANBK has become an effective instrument for measuring the quality of education in madrasas.